Melanie C. Hawthorne. Women, Citizenship, and Sexuality: The Transnational Lives of Renée Vivien, Romaine Brooks, and Natalie Barney. Liverpool UP, 2021. - Jennifer Carr (Studies in 20th & 21st Century Literature, 2022)
Review of Melanie C. Hawthorne. Women, Citizenship, and Sexuality: The Transnational Lives of Renée Vivien, Romaine Brooks, and Natalie Barney. Liverpool UP, 2021. 167 pp.
Keywords: Renee Vivien; Romaine Brooks; gender; sexuality; Natalie Barney